Metabolic engineering strategies for improvement of ethanol production in cellulolytic Saccharomyces cerevisiae. Issue 8 (13th August 2018) - Song, Xiaofei; Li, Yuanzi; Wu, Yuzhen; Cai, Miao; Liu, Quanli; Gao, Kai; Zhang, Xiuming; Bai, Yanling; Xu, Haijin; Qiao, Mingqiang
Abstract: As a traditional ethanol-producing microorganism, Saccharomyces cerevisiae is an ideal host for consolidated bioprocessing. However, expression of heterologous cellulase increases the metabolic burden in yeast, which results in low cellulase activity and poor cellulose degradation efficiency. In this study, cellulase-expressing yeast strains that could efficiently degrade different cellulosic substrates were created by optimizing cellulase ratios through a POT1 -mediated δ-integration strategy. Metabolic engineering strategies, including optimization of codon usage, promoter and signal peptide, were also included in this system. We also confirmed that heterologous cellulase expression in cellulosic yeast induced the unfolded protein response. To enhance protein folding capacity, the endoplasmic reticulum chaperone protein BiP and the disulfide isomerase Pdi1p were overexpressed, and the Golgi membrane protein Ca 2+ /Mn 2+ ATPase Pmr1p was disrupted to decrease the glycosylation of cellulase. The resultant strain, SK18-3, could produce 5.4 g L −1 ethanol with carboxymethyl-cellulose. Strain SK12-50 achieved 4.7 g L −1 ethanol production with phosphoric acid swollen cellulose hydrolysis. When Avicel was used as the substrate, 3.8 g L −1 ethanol (75% of the theoretical maximum yield) was produced in SK13-34. This work will significantly increase our knowledge of how to engineer optimal yeast strains for biofuel production from cellulosic biomass. Abstract : Multiple metabolic engineering strategies in cellulolytic yeast strains were combined to improve ethanol production from different cellulosic substrates.